Nonlinear Transformer with Variance Stabilization for Non-Gaussian Noise Suppression - V. A. Danilov; L. V. Danilova (Известия высших учебных заведений России: Радиоэлектроника, 2017)
The problem of approximation of nonlinear characteristic of weak signal detection in the form of polynomial function connected with integral distribution law is considered. The variance of this approximation does not depend on the kind and the parameters of the input non-Gaussian distribution. The article provides benchmarking of applying of polynomial function in case of sinusoidal noise when the noise is the sum of harmonic vibrancy and Gaussian noise. The noises with different spectral characteristics are analyzed. With radiofrequency noise spectrum the efficiency of the applied transformer may grow to considerably high values at the current stabilizing characteristics.